Assessment of Self-Healing Epoxy-Based Coatings Containing Microcapsules Applied on Hot Dipped Galvanized Steel - Karaxi, Evangelia K.; Kartsonakis, Ioannis A.; Charitidis, Costas A. (Frontiers in Materials, 2019)
This study focuses on the design, development and validation of two coating systems for corrosion protection of hot dip galvanized steel substrates. The coatings consist of epoxy-based resin reinforced with core-shell microcapsules, either cerium oxide or cuprous oxide core and a polymeric shell doped with cerium ions. The effect of the modification of the epoxy resin with a liquid rubber polymer has also been studied. Corrosion studies via electrochemical impedance spectroscopy (EIS) revealed that the coatings have enhanced barrier properties. Moreover, EIS studies on coatings with artificial scribes, demonstrated an autonomous response to damage and a self-healing effect. Heat-induced material re-flow has also been observed after exposure to temperature higher than the Tg of the system, which offered an additional self-healing mechanism, partially inhibiting the underlying corrosion processes when the liquid rubber is present in the system.